Alfalfa Costs and Returns in Central and Eastern Kansas - Fausett, Marvin R.; Warmann, Gerald W. (My University, 1997)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa production in central and eastern Kansas.
MF363_1997_10
Keywords: MF363; Economics; Crops; MF